Olmesartan-associated severe gastritis and enteropathy. Issue 1 (10th December 2018) - Shenbagaraj, Lavanya; Swift, Gillian
Abstract : Olmesartan is an angiotensin II receptor antagonist, used in the treatment of hypertension. We report a case of olmesartan-associated severe gastritis with enteropathy in a 74-year-old woman who presented with mainly upper gastrointestinal symptoms. There was significant endoscopic improvement in the mucosal inflammation on stopping the drug. Subsequent gastroscopy showed mucosal healing and normal gastric and duodenal mucosa. To our knowledge, this is the first case report of olmesartan-associated gastritis and enteropathy predominantly involving and affecting the whole of stomach with limited small bowel involvement.